PENGEMBANGAN PENUNTUN PRAKTIKUM VIRTUAL PADA BANDUL SEDERHANA DENGAN MODEL PEMBELAJARAN INKUIRI TERBIMBING - Mukuan, Grestia Elisa Amelia; Mandang, Theresje; Lolowang, Jimmy (Charm Sains: Jurnal Pendidikan Fisika, 2024)
This research was conducted with the aim to produce a product of amrita olabs practicum guide on simple pendulum material for class XI high school students in the science department. This research was conducted at SMA Negeri 1 Tompaso class XI IPA 3 with 20 students. Amrita olabs is the idea that laboratory experiments can be taught using the internet more efficiently and cheaper. Amrita olabs is one of the virtual experiment facilities in the virtual laboratory Amrita olabs can be used on labtop or cellphone androi/iphone and is a technological development in the field of education. This study uses the Research and Development (R&D) method with the 4D model in the data collection process carried out by validating the practicum guide. Based on the results of the analysis of the response of students after they use the Amrita olabs practicum guide, it is said to be good according to the average data of students' responses which can be seen from the gain value of 75%. Based on the results of the analysis of this study, it shows that the Amrita Olabs practicum guide is feasible to use in the learning process, especially in the practicum learning process and is able to improve the physics skills of students.